Abortion and conscientious objection: rethinking conflicting rights in the Mexican context. Issue 1 (1st January 2018) - Ortiz-Millán, Gustavo
ABSTRACT: Since 2007, when Mexico City decriminalized abortion during the first trimester, a debate has been taking place regarding abortion and the right to conscientious objection (CO). Many people argue that, since the provision of abortions (or "legal terminations of pregnancy" as they are called under Mexico City's law) is now a statutory duty of healthcare personnel there can be no place for "conscientious objection." Others claim that, even if such an objection were to be allowed, it should not be seen as a right, since talk about a right to CO may lead to a slippery slope where we may end up recognizing a right to disobey the law. In this paper, I argue that there is a right to CO and that this may be justified through the notions of autonomy and integrity, which a liberal democracy should respect. However, it cannot be an absolute right, and in the case of abortion, it conflicts with women's reproductive rights. Therefore, CO should be carefully regulated so that it does not obstruct the exercise of women's reproductive rights. Regulation should address questions about who is entitled to object, how such objection should take place, and what can legitimately be objected to.